POTENSI PEMBENTUKAN BISNIS SOSIAL UNTUK MENINGKATKAN AKSES PANGAN TERUTAMA SUMBER PROTEIN DI DESA KALIKIDANG KECAMATAN SOKARAJA KABUPATEN BANYUMAS - , Barokatuminalloh; Widayaningsih, Neni; Gunawati, Endang Sri (Prosiding, 2013)
This research is started because of the presence of food insecurity on poor household both in rural areas and in urban areas of Banyumas Regency. The main Cause limited income. The peopleâs acces to the foodstuffs is utmost important. The consumed foodstuffs have to fulfill every required nutrients. One of the food type that is less consumed is protein. The main cause is the limited acces. Kalikidang village of Sokarja Subdistrict is the carp farming centre Banyumas Regency. There are 33 farmers who are joined in fish farmers associations (POKDAKAN) âUlam Sariâ. The social busines which is a part of social entrepreneurship which is social or non profit oriented. This business is one of the solution for problems faced by people. The goal of this research is to identify various potential of pokdakan that can be base capital in establishing social business, and to identify the strength, weakness, opportunities, and threats of the potential and resources of Pokdakan. The data gatherng technique will be executed by observing, structured interviewing, while informant selection technique will be executed by snowball technique. The data analysis will be executed using internal external matrix (IE) analysis. The results showed that from analysis of internal condition has received seven factors of strenghth and five factors of weakness, also from external conditon has seven factors opportunities and seven factors threats in Pokdakan Ulam Sari. From analysis using IE matrix it has became known that Pokdakan Ulam Sari is located at I-cell. The strategy that can be executed is the grow and bulid strategy in the form of intensive strategy (market penetration, market development and product development) or integrative strategy (integration to rear, integration to front and horizontal integration). Those strategies can become alternatives, become base capital of establishing social business which aims to increase food security throught the increasing acces to protein sources. The Implicatin shows that the increase of resources quality especially in processing knowledge and technology of fish farming for facing the market competition. Also which change in paradigm of from self profit oriented to become group profit oriented, which will be embryo of social business establlishment to solve the acces to procure protein foodstuffs from fish.